Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1161/strokeaha.118.021732
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Bleeding During Acute Experimental Intracerebral Hemorrhage

Abstract: Background and Purpose: Mechanisms contributing to acute hematoma growth in intracerebral hemorrhage are not well understood. Neuropathological studies suggest that the initial hematoma may create mass effect that can tear vessels in the vicinity by shearing, causing further bleeding and hematoma growth. Methods: To test this in mice, we simulated initial intracerebral hemorrhage by intrastriatal injection of a liquid polymer that coagulates upon contact with tissue, and measured the presence and volume of ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Although we did not attempt to measure local pressures in order to avoid invasive instrumentation, mass effect and tissue distortion by expanding hematoma are characteristic of ICH 36 and can even shear local arterioles causing secondary hemorrhage. 37 Collagenase itself did not directly trigger SD because SDs occurred with a latency of 30 min or more and coincided with rapid hematoma growth. Moreover, perihematomal edema and inflammation occur many hours to days after ICH and are unlikely to have contributed to SD occurrence in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not attempt to measure local pressures in order to avoid invasive instrumentation, mass effect and tissue distortion by expanding hematoma are characteristic of ICH 36 and can even shear local arterioles causing secondary hemorrhage. 37 Collagenase itself did not directly trigger SD because SDs occurred with a latency of 30 min or more and coincided with rapid hematoma growth. Moreover, perihematomal edema and inflammation occur many hours to days after ICH and are unlikely to have contributed to SD occurrence in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous intracerebral microhemorrhages (CMHs) are defined as small foci of hemorrhages in the cerebrum [ 30 32 ]. These atraumatic CMHs are due to the rupture of small arteries, arterioles, and/or capillaries.…”
Section: Introductionmentioning
confidence: 99%
“…Lauer et al [90] also found that the pretreatment with dabigatran etexilate, a new oral specific thrombin inhibitor, did not increase hematoma volume in both collagenase-induced and laser-induced ICH models, in contrast to warfarin. In contrast, another study suggested both warfarin and dabigatran exacerbated secondary hemorrhage in two kinds of mouse ICH model (intrastriatal liquid polymer injection and intrastriatal blood injection) [91]. Further investigation is needed for a better understanding of the pathophysiology of thrombin-induced brain injury after ICH to determine how and when to target it (or downstream pathways) without impacting hematoma growth.…”
Section: Thrombin In Intracerebral Hemorrhagementioning
confidence: 99%